A study of factors influencing Chinese college students’ intention of using metaverse technology for basketball learning: Extending the technology acceptance model - Ren, Longfei; Yang, Fangfang; Gu, Chao; Sun, Jie; Liu, Yunfeng (Frontiers in Psychology, 2022)
Abstract: The purpose of this study is to investigate the possibility of combining metaverse technology with basketball teaching under COVID-19.On the basis of the TAM model, this study examined 849 valid samples, used structural equation modeling for verification, and examined the moderating effect of gender on the path relationship. In this study, we found that perceived ease of use, flow experience, and perceived usefulness are important factors in predicting behavioral intentions.Perceived usefulness and flow experience significantly affect attitude, and gender moderates the relationship between perceived ease of use and behavioral intentions.Overall, this study contributes to theoretical research on the use of Metaverse technology in basketball teaching combined with TAM, and examines the role of flow and gender in the teaching process.